2020
DOI: 10.1002/ijfe.2406
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effectiveness of foreign aid on the development of Africa

Abstract: Foreign aid with the aim of propagating growth and development in developing countries has been in existence since the end of World War II. Africa as the recipient of aid over this period is still wallowing in poverty and underdevelopment. This phenomenon has interested many researchers and donor agencies to unravel the true impact of aid to the developmental agenda of Africa but the findings are mixed and inconsistent. Our study focused on 50 African countries for the period

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…By contrast, Brumm (2003) and Rajan and Subramanian (2005) document that aid does not facilitate growth even in recipient countries with relatively good economic policies. The results of Hongli and Vitenu‐Sackey (2020) and Leeson (2008) support the view that aid fails to facilitate growth and may even retard it. However, Dreher et al (2021) and Yusuf (2012) document a positive and significant impact of aid on growth and emphasize that the estimated effect is not conditional on the recipient countries' policy environment.…”
Section: Introductionmentioning
confidence: 80%
“…By contrast, Brumm (2003) and Rajan and Subramanian (2005) document that aid does not facilitate growth even in recipient countries with relatively good economic policies. The results of Hongli and Vitenu‐Sackey (2020) and Leeson (2008) support the view that aid fails to facilitate growth and may even retard it. However, Dreher et al (2021) and Yusuf (2012) document a positive and significant impact of aid on growth and emphasize that the estimated effect is not conditional on the recipient countries' policy environment.…”
Section: Introductionmentioning
confidence: 80%
“…Once stationarity and cointegration have been established, a correlation matrix is employed to evaluate the relationship between the dependent and independent variables, as well as to identify potential signs of multicollinearity. Multicollinearity refers to the condition wherein there exist multiple independent variables that exhibit correlation coefficients exceeding the threshold of -/+0.70 Jiang Hongli & Vitenu-Sackey, 2019;J. Hongli & Vitenu-Sackey, 2020;Vitenu-Sackey, 2020;Vitenu-Sackey & Barfi, 2021;.…”
Section: Methodology and Datamentioning
confidence: 99%
“…They found that critical variables such as income and consumer credit can promote consumption levels. Jiang and Jiang [ 2 ] conducted a heterogeneity test and found that DFI has a more substantial promoting effect on rural areas than urban ones. Therefore, residents' consumption level and structure could be improved by narrowing the urban-rural income gap and optimizing industrial structure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers study consumption upgrading by increasing total consumption and optimizing consumption structure to investigate consumption potential [ 2 , 3 ]. Existing research indicates that consumption levels have improved to some extent, however, because of the significant gap in economic development under the urban-rural dual system, rural residents' total consumption expenditure and structure levels are lower than those of urban residents [ 4 ].…”
Section: Introductionmentioning
confidence: 99%